Unlocking survival mechanisms for metal and oxidative stress in the extremely acidophilic, halotolerant Acidihalobacter genus. - Khaleque, Himel; Fathollahzadeh, Homayoun; Gonzalez, Carolina; Shafique, Raihan; Kaksonen, Anna; Holmes, David; Watkin, Elizabeth (mpdi, 2020)
Microorganisms used for the biohydrometallurgical extraction of metals from minerals must be able to survive high levels of metal and oxidative stress found in bioleaching environments. The Acidihalobacter genus consists of four species of halotolerant, iron–sulfur-oxidizing acidophiles that are unique in their ability to tolerate chloride and acid stress while simultaneously bioleaching minerals. This paper uses bioinformatic tools to predict the genes and mechanisms used by Acidihalobacter members in their defense against a wide range of metals and oxidative stress. Analysis revealed the presence of multiple conserved mechanisms of metal tolerance. Ac. yilgarnensis F5T, the only member of this genus that oxidizes the mineral chalcopyrite, contained a 39.9 Kb gene cluster consisting of 40 genes encoding mobile elements and an array of proteins with direct functions in copper resistance. The analysis also revealed multiple strategies that the Acidihalobacter members can use to tolerate high levels of oxidative stress. Three of the Acidihalobacter genomes were found to contain genes encoding catalases, which are not common to acidophilic microorganisms. Of particular interest was a rubrerythrin genomic cluster containing genes that have a polyphyletic origin of stress-related functions.